A novel 2-stage dish concentrator with improved optical performance for concentrating solar power plants. (August 2017) - Wang, Jun; Yang, Song; Jiang, Chuan; Yan, Qianwen; Lund, Peter D.
Abstract: Here we propose a novel 2-stage dish concentrator system for concentrating solar power plants based on the so-called overlap method, which improves both the radial flux concentration ratio (β) and the intercept factor (γ) of the concentrator. The 2-stage dish is composed of paraboloid primary and hyperboloid secondary mirrors having a special hollow structure enabling the mirrors to overlap, but avoiding excess shading. Geometric and optical analyses with ray-tracing show maximum values of β = 15, 498 and γ = 0.78. Also, the size of the focal spot could be reduced. The concept is applicable for solar tower concepts enabling more compact unit mirrors and reducing the receiver size. Graphical abstract: Highlights: A novel 2-stage 4-mirror dish concentrator is proposed. Overlapping method is used for mirror optimization. High concentration ratio and intercept factor was achieved with the new design. The new concentrator has a compact mirror design and reduces receiver size.